The Effect of Compensation on Employee Organizational Commitment at PT. Vale Tbk in Sorowako - Musa, Chalid Imran; Tawe, Amiruddin (PT. Maju Malaqbi Makkarana, 2023)
The Effect of Compensation on Employee Organizational Commitment of PT. Vale Tbk in Sorowako. The purpose of this study was to determine the Effect of Compensation on Employees' Organizational Commitment at PT. Vale Tbk in Sorowako. This type of research is quantitative research. The number of samples in this study were 60 employees who were employees in the Maintenance Department of PT. Vale The results of the study after the data were processed showed that there was a positive influence between the financial compensation (X1) and non-financial compensation (X2) variables on the Organizational Commitment variable (Y) which can be shown through the results of the T test, namely variable X1 has variable X1 has t count 4.653 > 2.002 (t table) and sig. 0.000 < 0.05. Variable X2 has a t count of 3.392 > 2.002 (t table) and a sig. 0.000 < 0.05.